Aspect ratio-controlled preparation of α-CaSO4·0.5H2O from phosphogypsum in potassium tartrate aqueous solution. Issue 38 (11th July 2019) - Sun, Xiangbin; Zhang, Genlei; Cui, Peng
Abstract : The conversion of industrial gypsum to rod-shaped α-CaSO4 ·0.5H2 O crystals with tunable aspect ratio in a H2 O system is realized with potassium tartrate. Abstract : In this study, a simple and efficient strategy is developed to synthesize rod-shaped α-CaSO4 ·0.5H2 O crystals with tunable aspect ratio from industrial phosphogypsum only in potassium tartrate aqueous solution at a low temperature. Industrial phosphogypsum can be effectively converted into rod-shaped α-CaSO4 ·0.5H2 O crystals with the assistance of potassium tartrate, and the aspect ratio of α-CaSO4 ·0.5H2 O crystals gradually decreases from 52 : 1 to 1 : 1 with increasing the concentration of potassium tartrate. The formation process of the rod-shaped α-CaSO4 ·0.5H2 O crystals in this system involves the dissolution of CaSO4 ·2H2 O and nucleation of α-CaSO4 ·0.5H2 O crystals. The tartrate ions from potassium tartrate in this system preferentially bind to (001) and (002) facets of α-CaSO4 ·0.5H2 O crystals, inhibiting the growth of α-CaSO4 ·0.5H2 O crystals along the c -axis and controlling its morphology and aspect ratio.